2018
DOI: 10.1080/00140139.2018.1429674
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependence of discomfort caused by vibration and mechanical shocks

Abstract: The frequency content of a mechanical shock is not confined to its fundamental frequency, so it was hypothesised that the frequency-dependence of discomfort caused by shocks with defined fundamental frequencies will differ from the frequency-dependence of sinusoidal vibration. Subjects experienced vertical vibration and vertical shocks with fundamental frequencies from 0.5 to 16 Hz and magnitudes from ±0.7 to ±9.5 ms. The rate of growth of discomfort with increasing magnitude of motion decreased with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The body vibration will be transmitted to the human body through seats, pedals, joystick and other components, thus causing discomfort to the human body. Working in this environment for a long time will reduce the sensitivity of the driver, increase the threshold value of vibration sense, and cause bone joint damage, bone hyperplasia, muscle atrophy and other adverse effects, thereby threatening the driver’s health [ 10 13 ]. At the same time, poor vibration will not only reduce crop yield, but also harm the reliability of the machinery itself [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The body vibration will be transmitted to the human body through seats, pedals, joystick and other components, thus causing discomfort to the human body. Working in this environment for a long time will reduce the sensitivity of the driver, increase the threshold value of vibration sense, and cause bone joint damage, bone hyperplasia, muscle atrophy and other adverse effects, thereby threatening the driver’s health [ 10 13 ]. At the same time, poor vibration will not only reduce crop yield, but also harm the reliability of the machinery itself [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…All road vehicles interact with the ground by the tires contact, that transmits to the chassis the excitation due to the track profile. The suspension system has the main function to attenuate those excitations to provide ride comfort [1], since the vibrations felt by the driver are very related to comfort, being this a main contributing factor to vehicle purchase decision and satisfaction [2,3] in the case of commercial vehicles. The study of suspension performances is usually approached by the construction of mathematical models representing the vehicle and its properties [4], considering very simple models with two degrees-of-freedom models in quarter-car models [5][6][7], or increasing the model size to represent the full vehicle [4,[8][9][10][11], aiming to explore the effect of excitation on other points on the ride model.…”
Section: Introductionmentioning
confidence: 99%
“…As such, few evaluation methods have been established based on field test results, and this is increasingly becoming a problem. Laboratory tests mostly adopt consecutive sinusoidal excitation as the input, whereas most excitations in actual field tests are non-sinusoidal and non-consecutive -they are random or quasi-random [9,10], so the suitability of directly applying laboratory-based methods to actual field test scenarios is in doubt. Mansfield et al [11] found that the correlation strength between several vibration evaluation methods and normalized subjective discomfort scores is strongly influenced when excitation type changes from non-random to random or quasi-random.…”
Section: Introductionmentioning
confidence: 99%
“…Griffin [25] suggested that using an average operator in the time zone is oversimplistic because it can result in excessive estimation for short durations or apparently unreasonably low estimation for long durations; periods containing different magnitudes, transients, and shocks in varying vibration exposure must be defined. Standardizing the total integration time can solve this problem, but it is almost impossible to achieve [10,26]. Secondly, a maximum operator is adopted as the main logic to integrate vibration information.…”
Section: Introductionmentioning
confidence: 99%